2003
DOI: 10.1002/ijc.11078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lifetime lactation on breast cancer risk: A Korean Women's Cohort Study

Abstract: The objective of our study was to examine the effect of lifetime lactation on breast cancer risk among premenopausal women. The data were from a prospective cohort study with a follow-up period of 6 years in Korea (1995Korea ( -2000 Although the protective effect of lactation on breast cancer has been discussed among researchers for more than 20 years, no study ever found a detrimental effect of breastfeeding on risk of breast cancer. For example, an inverse association between lifetime lactation and breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 24 publications
5
42
0
5
Order By: Relevance
“…It is known that breastfeeding reduces the risk for breast cancer (15,45,48) and women who do not breastfeed have a higher risk for breast cancer (45,48). It was identified in our study that 95.5% of women breastfed their children (Table 3).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…It is known that breastfeeding reduces the risk for breast cancer (15,45,48) and women who do not breastfeed have a higher risk for breast cancer (45,48). It was identified in our study that 95.5% of women breastfed their children (Table 3).…”
Section: Discussionmentioning
confidence: 53%
“…Early menarche, late menopause, not having given birth or having given birth for the first time after the age of 30 prolong the period during which oestrogens influence the breast tissue (44,45). Therefore, early menarche, childbirth before the age of 30, breastfeeding and early menopause reduce the risk for breast cancer (39).…”
Section: Discussionmentioning
confidence: 99%
“…4,7,[11][12][13][14] A protective effect of breastfeeding on the risk of premenopausal breast cancer has been observed in several studies, although not in all analyses. [31][32][33][34][35][36][37] Although the small size of this cohort prohibits analysis of the possibility that lactation might be protective, further studies in larger survivor cohorts may be indicated. Even if no sanguine effect on maternal health can be determined, breastfeeding has clear benefits for infant health.…”
Section: Discussionmentioning
confidence: 99%
“…81,82 Maternal Health Benefits Important health benefits of breastfeeding and lactation are also described for mothers. 83 The benefits include decreased postpartum bleeding and more rapid uterine involution attributable to increased concentrations of oxytocin, 84 decreased menstrual blood loss and increased child spacing attributable to lactational amenorrhea, 85 earlier return to prepregnancy weight, 86 decreased risk of breast cancer, [87][88][89][90][91][92] decreased risk of ovarian cancer, 93 and possibly decreased risk of hip fractures and osteoporosis in the postmenopausal period. [94][95][96] …”
Section: Neurodevelopmentmentioning
confidence: 99%